Optimization of Supply Chain Management in the Russian Federation Concerning Financial Investment and The Practice of Its Enforcement - A. V. Ivanchin; A. A. Knyazkov (International Journal of Supply Chain Management, 2020)
Abstract— Extensive economic, productive and commercial developments in the present era have forced businesses to actively participate in network and supply chain chain-based economies. The tendency towards this approach, although it has brought advantages and profitability for network member firms and supply chains, has also led to many problems and complexities for managing the financial flows, liquidity and working capital of their firms and business partners. Last time the alarming situation, prevailing in Russia in the sphere of activity of